Empowering Acute Coronary Syndrome Patients: Assessing Self- Motivation, Self-Belief, and Self-Management Readiness (Bangladesh Journal of Medical Science, 2026)
Self-management readiness is needed for acute coronary syndrome patients to improve health behavior to prevent recurrence. The aim of the research was to analyze the influence of self-motivation and self-belief on self-management readiness in acute coronary syndrome patients. The research design uses a cross-sectional study. A sample of 145 SKA patients was taken using accidental sampling technique. The variables measured are self-motivation, selfbelief and self-management readiness. The research instrument used a questionnaire. Data were analyzed using a linear regression test. The results showed that self-motivation had an effect on participation (0.003), self-motivation and perceived threat had an effect on therapeutic alliance (0.013; 0.057), self-motivation and perceived threat had an effect on goal setting (0.011; 0.003), self-motivation influence on selfevaluation (0.005) and self-motivation and perceived threat influences emotional control (0.003; 0.002). Conclusion: High self-motivation and increasing perceived threat in ACS patients have an impact on increasing self-management readiness. The practical implication of this research is the need for education from health workers, especially doctors and nurses, to increase self-motivation so that self-management readiness can increase. It is hoped that increasing self-management readiness will increase better health behavior so that there will be a reduction in relapses in patients.BJMS, Vol. 25 No. 01 January’26 Page : 103-111